Addressing the ongoing threat of antimicrobial resistance: synthetic investigations of novel amicetin and B-lactam antibiotics - Bhana, Ashlyn (Department of Chemistry, 2025)
Antimicrobial resistance (AMR) poses a significant risk to global health security and threatens to undermine a century of healthcare gains. Within this thesis, we attempt to address the ongoing threat of AMR through performing synthetic investigations of amicetin and novel -lactam therapeutics. Chapter 1 essentially highlights the role and importance of synthesizing complex chiral scaffolds and heterocycles in discovering new antibiotics by providing a brief historical context and background of disease etiology and medicine (chemotherapy), AMR, -lactam antibiotics, heterocyclic chemistry, and green chemistry techniques such as organocatalysis and visible-light photocatalysis, which were utilized to synthesize the relevant compounds described in this study. Chapter 2 provides background on the natural antibiotic, amicetin, and a current literature review on the synthesis of -tertiary amines (ATAs), focusing mainly on the electrophilic amination strategy, which was relevant to this study. Chapter 2 also provides the aims and objectives for Chapter 3. Chapter 3 discusses the results obtained within the first project of this study, namely the attempted synthesis of p-aminobenzoic acid (PABA)--methyl-L-serine substructure of amicetin, from PABA as the starting point. Synthetic access to the PABA--methyl-L-serine moiety would allow for structure-activity relationship (SAR) studies to be performed on the natural antibiotic. This synthetic route involved a Cinchona alkaloid organocatalyzed electrophilic hydrazination of a novel -dicarbonyl system, namely -formylamides (AFAs), with azodicarboxylates. Novel AFAs are synthesized via a Ti-Claisen condensation between methyl formate, a methodology also previously developed within our research group. Unfortunately, due to difficulties encountered within the initial synthetic route and time constraints, we could not reach the PABA--methyl-L-serine end-target. However, the adjusted synthetic route devised to reach the end-target seems highly feasible and forms part of the future work for this project. Instead, we showcased the synthetic utility of our aminated products by functionalizing them into N-amino oxazolidinones and oxazolidinones, which may find applications in asymmetric synthesis. Chapter 4 provides a brief introduction to monobactams and a brief current literature review of the synthesis of 2-azetidinones. Chapter 4 also provides the aims and objectives for Chapter 5. Chapter 5 discusses the results obtained within the second project of this study, namely the synthesis of novel 2-azetidinones via a radical photocyclization of acrylamides enabled by triplet energy transfer visible-light photocatalysis, a methodology which was also previously developed within our research group, and investigation into their antimicrobial activity. Although the preliminary bioactivity data of the synthesized 2-azetidinones against WT Staphylococcus aureus ATCC 49775 was disappointing, it should be noted that the project is still well in its infancy, and further investigation and evaluation is warranted to assess whether the scaffold is worth pursuing for potential antimicrobial activity or other biological applications.